Koncepcje merkantylistyczne a ich wykorzystanie w Republice Zjednoczonych Prowincji - Strobel, Joanna (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The Republic of the Seven United Provinces is seen in the literature as a state favouring free trade, which enabled it to achieve a dominant position in colonial trade between the 16th and 18th centuries. However, even this country used mercantilism-inspired solutions. Given the specific nature of its economy, the Republic was particularly attached to a positive balance of trade. On the other hand, it undertook short-term actions in line with the principle of interventionism and protectionist customs policy — guided on each occasion by particular interests of groups holding power. Consequently, the Republic used the principles of mercantilism only to an extent it found suitable in a given political and economic situation
Keywords: merkantylizm; Holandia; gospodarka; ekonomia; finanse